Development and application of a dietary program to reduce sugar intake using a living lab approach in Korea: an intervention study - Jung-Hyun Kim; Min Sook Kyung; Seul Ki Choi (Korean Journal of Community Nutrition)
Objectives This study aimed to develop and apply a dietary program to reduce sugar intake among community residents using a Living Lab approach. Methods We developed and applied a community-based dietary program to reduce sugar intake. Participants were recruited from community organizations, including a children’s food service management center, elementary to high schools, a university, a family center, a community health center, and an elderly welfare center. The dietary program was conducted in two phases; start and next levels. The start level included a pre-assessment of dietary behaviors and participation in educational platforms, whereas the next level included activities using educational platforms, tailored mission and feedback, and pre- and post-surveys. Extension educators at each community organization implemented the dietary program following organization-specific guidelines. Changes in participants’ nutrition knowledge, dietary behaviors and perceptions, self-efficacy, intention to reduce sugar intake, and participants’ program satisfaction were analyzed using paired t-tests. Results In total, 1,238 and 339 individuals participated in the start and next level, respectively. Participants reported significantly lower scores on dietary behavior items regarding drinking more juice or soft drinks after program participation (P = 0.009) and craving sweet foods (P = 0.046). They reported a higher intention to take interest in sugar content in food (P = 0.009) and lower-sugar recipes (P = 0.019), eat less food with high sugar content (P = 0.020), and drink water or sparkling water instead of soft drinks (P = 0.042). Nutrition knowledge did not significantly change after program participation. Program satisfaction significantly increased from the start level to the next level (P<0.050). Conclusion This study showed the potential of using a Living Lab approach to implement community-wide dietary interventions. Further research is required to evaluate the effectiveness of the Living Lab approach in various community settings.